Unilateral versus bilateral hearing aids for bilateral hearing impairment in adults - Browning, George G.; Howell, Patrick; Whitmer, William M.; Ftouh, Saoussen; Chong, Lee Yee; Naylor, Graham (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of bilateral versus unilateral hearing aids in adults with a bilateral hearing impairment.